The route out of the routine: where do the displaced routine workers go? - Holmes, C (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2011)
Over the previous three decades, technological progress has driven a shift in the occupational structure of many countries, including the UK. Some jobs are comprised of a number of tasks which could be replaced by information and communications technology capital. These jobs are referred to as routine in the sense that the tasks performed by workers in them tend to follow a series of instructions, which could be replicated by an appropriately programmed machine. This process is often referred to as routinisation (Autor, Levy and Murnane 2003). Along with the related phenomena of polarisation, much of the discussion has been on the implications of these changes for wage inequality (Goos and Manning 2007, Autor, Katz and Kearney 2006a). However, changes in the occupational structure have potentially important effects on mobility as well, but as yet these effects have not been rigorously analysed. With improving upward mobility often mentioned as an ambition of successive governments, it is important to establish what barriers exists in order to devise policies to overcome them. One aspect of changes to mobility prospects can be examined by looking at the labour market outcomes of employees displaced by routinisation. A key question is whether these workers are able to move to well-paid non-routine jobs, and if they are, what factors contribute to this upward mobility? Using data from the National Child Development Study (NCDS), this paper presents a mobility analysis of these routine workers between 1981 and 2004. As expected, periods where the employment share of routine jobs fell markedly across the entire economy were periods which witnessed increased mobility of routine workers towards both high and low wage non-routine jobs. The relationship between routinisation and mobility is mediated through the qualification levels, specific skills and experience of workers.